2010
DOI: 10.1088/0957-4484/21/45/455605
|View full text |Cite
|
Sign up to set email alerts
|

Low- and high-temperature controls in carbon nanofiber growth in reactive plasmas

Abstract: A numerical growth model is used to describe the catalyzed growth of carbon nanofibers in the sheath of a low-temperature plasma. Using the model, the effects of variation in the plasma sheath parameters and substrate potential on the carbon nanofiber growth characteristics, such as the growth rate, the effective carbon flux to the catalyst surface, and surface coverages, have been investigated. It is shown that variations in the parameters, which change the sheath width, mainly affect the growth parameters at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
60
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(63 citation statements)
references
References 53 publications
3
60
0
Order By: Relevance
“…(2)-(9), (13), (15), and (16) simultaneously for the charging of the CNT and for the kinetics and energy balance of electrons, ions, neutrals, and the cylindrical CNT surface with appropriate boundary conditions, viz., at s ¼ 0, n ct ¼ 10 4 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…(2)-(9), (13), (15), and (16) simultaneously for the charging of the CNT and for the kinetics and energy balance of electrons, ions, neutrals, and the cylindrical CNT surface with appropriate boundary conditions, viz., at s ¼ 0, n ct ¼ 10 4 …”
Section: Resultsmentioning
confidence: 99%
“…The effects of catalyst, growth temperature, and the density of participating species, etc., have been extensively studied. [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15] Sodha et al 1 in their theoretical model, have investigated the growth of embryonic dust particles in a complex plasma and found that the radius of the embryonic dust grains decreases with the number density of dust particles.…”
Section: Introductionmentioning
confidence: 99%
“…A sheath model was developed to quantify the plasma-sheathrelated effects on the CNF growth characteristics. 40 A hybrid molecular dynamics/force-biased Monte Carlo simulations explained the growth mechanism and clarified the chirality formation of SWCNT on a substrate-bound Ni40 cluster. 41 The SWCNT nucleation mechanism on Au catalyst nanoparticles on a Si substrate exposed to the reactive plasma in a Ar þ H 2 þ CH 4 gas mixtures was also reported.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous works have been done to highlights the role of temperature on the growth of CNTs. [8][9][10][11][12][13][14][15] Han et al 8 have demonstrated that as the growth temperature increases, the average diameter of CNTs increased from 40 to 110 nm and the growth rate was enhanced from 2 to 15 lm/h. Baratunde et al 9 have shown that as the growth temperature was decreased, the associated decrease in CNT density and average CNT diameter resulted in an increased thermal resistance at the interface.…”
Section: Introductionmentioning
confidence: 99%
“…[12][13][14][15] Denysenko et al 12 have studied the growth of single walled CNTs (SWCNTs) in a PECVD using the surface deposition model. In this case, it was shown that at low substrate temperatures (1000 K), the atomic hydrogen and ion fluxes from the plasma could strongly affect the nanotube growth.…”
Section: Introductionmentioning
confidence: 99%